PROSEDUR MEMBERSIHKAN DAN MENYIAPKAN KAMAR MANDI PADA ROOM SECTION HARRIS RESORT WATERFRONT BATAM - Santoso, Muhammad Alfin; Siddiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The room is one of the main products in a hotel, therefore the cleanliness of the bedroom alone is not enough to support it. The bathroom also in a room must also be considered cleanliness, neatness, comfort, and completeness so as to create a quality hotel room. This research method uses qualitative methods, by making observations at Harris Resort Waterfront Batam, interviewing staff at the Housekeeping Department, and taking some documentation as an overview of the research. From these data collection techniques, it is produced how porsedur sets aside and prepare, as well as what obstacles are contained in the process of cleaning the bathroom at Harris Resort Waterfront Batam. From the human resources and knowledge contained in Harris Resort Waterfront Batam, this supports the resolution of existing problems and is able to implement procedures very well. Keywords: Hotel Room, Procedure, Bathroom